2010
DOI: 10.1248/cpb.58.950
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identification of a New Tri-p-coumaroylspermidine with Serotonin Transporter Inhibition from Safflower

Abstract: Safflower (Carthamus tinctorius L.), a member of the family Compositae, geologically distributes in all regions in China, and is utilized for producing herbal medicines for the treatment of inflammatory diseases, hyperlipemia, arteriosclerosis, gynecological disorders, and osteoporosis. 1) To date, it has been known to contain flavonoids, 2) cartharmin, safflower yellow A, quinochalone, safflomin, cartorimine, alkaloids, 3) lignans, fatty acids, 4) triterpene alcohols, 5) and serotonin derivatives.6-8) Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…29 Several methylene proton signals at δ 1.55− 1.95 (internal), δ 3.09−3.38 (bound to end amine nitrogen), and δ 3.18−3.58 (bound to internal amine nitrogen) and the corresponding carbon signals at δ 25.5−29.8, 37.8−38.3, and δ 39.7−47.7 confirmed the presence of spermidine molecules conjugated with phenolic acids. 30 Thus, the main compound found in the methanol/ethanol soluble fractions was tri-pcoumaroylspermidine 31 accompanied by other HCAA of spermidine and putrescine. LC−MS analyses confirmed exact masses of 584.27540 [M + H] + and m/z 438.23864 [M + H] + corresponding to tri-and di-p-coumaroylspermidines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…29 Several methylene proton signals at δ 1.55− 1.95 (internal), δ 3.09−3.38 (bound to end amine nitrogen), and δ 3.18−3.58 (bound to internal amine nitrogen) and the corresponding carbon signals at δ 25.5−29.8, 37.8−38.3, and δ 39.7−47.7 confirmed the presence of spermidine molecules conjugated with phenolic acids. 30 Thus, the main compound found in the methanol/ethanol soluble fractions was tri-pcoumaroylspermidine 31 accompanied by other HCAA of spermidine and putrescine. LC−MS analyses confirmed exact masses of 584.27540 [M + H] + and m/z 438.23864 [M + H] + corresponding to tri-and di-p-coumaroylspermidines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The identification of the compounds (Figure 1) corresponding to each peak was confirmed by comparing NMR, HRESI-MS data obtained by UPLD-ESI-TOF-MS, previous papers, and 2D NMR spectra. 32,33,37 Compounds corresponding to four peaks were isolated and identified as N 1 ,N 10 ,N 5 -(Z)-tri-p-coumaroylspermidine (4), N 1 -(E)-N 5 ,N 10 -(Z)-tri-p-coumaroylspermidine (5), N 1 ,N 10 -(E)-N 5 -(Z)-tri-p-coumaroylspermidine (6), and N 1 ,N 10 ,N 5 -(E)-tri-p-coumaroylspermidine (8) (Figure 2). The compound 7 (a mixture of two compounds) and a small peak between the compounds 4 and 5 in HPLC chromatogram all have the same UV spectrum with a UV max at around 300 nm and the same molecular weight as the above-described tri-pcoumaroylspermidines, probably corresponding thus to other stereoisomers of tri-p-coumaroylspermidine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, spermidine hydroxycinnamate conjugates have antioxidant [31, 32], antibacterial [33], antiviral [34], insecticidal [35] and antiparasitic [36] activities. Other studies have demonstrated the inhibitory activity of polysubstituted p -coumaroyl polyamines on brain transporters for which a genetic polymorphism is associated with psychological disorders [37, 38]. For this experiment, we selected the BAHDs p -coumaroyl-CoA:spermidine (AtSCT) and sinapoyl-CoA:spermidine (AtSDT) transferases from Arabidopsis [39], and p -coumaroyl-CoA:agmatine transferase (HvACT) from barley ( Hordeum vulgare ) [40].…”
Section: Resultsmentioning
confidence: 99%